Kebijakan Pemerintah dalam Kegiatan Shalat Berjamaah di Masa Pandemi Covid-19 - Fahiza, Zihan; Siti Nur Zalikha (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The Covid-19 pandemic is the largest disease outbreak that occurred from 2019 to 2020, therefore the government itself issued policies related to policies. one of which is related to congregational prayer activities during the pandemic. The emergence of policies related to congregational activities inevitably raises pros and cons among the community. When a region carries out large-scale social activities (PSBB), it disturbs every activity related to religion. The method used here is juridical normative and uses qualitative data analysis techniques. each policy formulation that is responsible for membership registered in a meeting arranged hierarchically.